"Regardless of Their Gender": Descriptions of Sexual Identity among Bisexual, Pansexual, and Queer Identified Individuals. Issue 1 (2nd January 2017) - Galupo, M. Paz; Ramirez, Johanna L.; Pulice-Farrow, Lex
ABSTRACT: The present research investigates the way individuals under the bisexual umbrella conceptualize their sexual identity. Participants included 172 adults who self-identified as bisexual, pansexual, and queer. Participants individually completed an online survey in which they were asked to describe their sexual identity. Qualitative responses were analyzed via thematic analysis. Four major themes were identified and found relevant to all three identity groups: (1) labeling sexual identity, (2) distinctions of attraction, (3) explicit use of binary/nonbinary language, and (4) identity transcendence. Each of the four major themes was further composed of subthemes, and one minor theme of questioning also emerged. Patterns of responses across sexual identity were analyzed via chi-square analyses. Individuals who self-identified as bisexual, pansexual, and queer demonstrated similarities and differences in the way they described their sexual identities. Of the 15 emergent subthemes, six differed in frequency across sexual identity. Discussion focuses on elucidating when grouping bisexual, pansexual, and queer identities together may prove useful, and when it may further distort an understanding of the range of plurisexual experience.